Promosi Kesehatan Penyakit Menular Dan Tidak Menular Pada SMPLB Menggunakan Metode Permainan Edukatif Flash Card - Silviana Pusparindi Anindita; Arika Tri Afrika Sari; Kharisma Siskha Aprilia; Yuli Widyastuti; Nurul Istiqomah; Heni Purwaningsih (Pakis Journal Institute, 2024)
ABK (Children with Special Needs) are children who have physical, intellectual and emotional characteristics that are lower or higher than normal children their age. ABK can also be defined as children who have weaknesses and disabilities. Limited knowledge of crew members, especially in maintaining health, can reduce the health status of ABK. The community service carried out is one of the interventions that can be provided, the focus of the problem is regarding understanding infectious and non-infectious disease using the flash card educational game method. This health promotion aims to increase ABK knowledge about health so that they can reduce morbidity rates due to infectious and non-infectious disease. Using educational flash card games is one of innovations used in community service, adapting the learning by playing method. The level of knowledge of the 30 respondents was proven to have increased, which was measured through pre and post test questionnaires. The average post test score increased or was higher after providing health education using educational flash card games, namely from 37.7 to 65.6. There was an increase in understanding and knowledge of SMPLB students and students about infectious and non-infectious disease by 53.3% after being given health education using the flash card educational game method. The flash card educational games method is effective for use in the teaching and learning process and also as innovation in delivering material in community service to ABK respondents.